Heritage preservation of Jerantut: reliving cultural value old town Jerantut/ Aqil Syahmi Mohd Sibee - Mohd Sibee, Aqil Syahmi (2019)
Cultural heritage is important because it strongly influences our sense of identity, our loyalties, and our behavior. Memory institutions (archives, libraries, museums, schools, and historic sites) have a responsibility for preserving and interpreting the cultural record, so there are practical reasons to study cultural heritage. Attention to cultural heritage leads to wider awareness of the complexity and cultural bases of archives, libraries, and museums. Specialized terms are explained. The role of time is discussed and the past, history, and heritage are distinguished. Cultural heritage has some specialized legal and economic consequences and is deeply associated with much of the conflict and destruction in the world. After nearly a half century of suburbanization, economic development specialists and urban planners have begun to appreciate the unique aesthetic and heritage landscapes of underutilized downtown areas as potential geographic spaces for economic growth. Consequently, fostering heritage tourism and recreation industries that take advantage of these unique spaces has become a cornerstone of many downtown redevelopment plans. A growing pool of literature on the subject of sustainable tourism has noted that heritage tourism is ideologically and institutionally different from other forms of the industry, as concepts of long term planning, cultural awareness and resource conservation are important to both tourism sustainability and heritage management.